African Elections as a Testing Ground: Comparing Coverage of Cambridge Analytica in Nigerian and Kenyan Newspapers. Issue 4 (2nd October 2019) - Ekdale, Brian; Tully, Melissa
ABSTRACT: In March 2018, British and American news outlets published extensive reporting on Cambridge Analytica's (CA) ethically and legally questionable activities in political campaigns around the world. This reporting primarily focused on three issues: data privacy and protection, unethical political campaigning on social media, and foreign involvement in national elections. While much attention has been paid to CA's work in the US and UK, these exposés also provided details about CA's work in presidential elections in Nigeria and Kenya. Because little attention has been paid to CA's work in Africa, we conducted a qualitative textual analysis of four Nigerian and Kenyan newspapers to understand how media in these countries grappled with CA's role in their respective presidential elections. Our findings demonstrate, first, that newspaper coverage in both countries relied heavily on international reporting, and second, while Nigerian newspapers covered the scandal as an intranational conflict between competing political parties, the Kenyan press wrestled with the scandal's implications for the country's democratic institutions.